Product Isomer Distribution in the Sequential Functionalization of Cyclic PIII2N2 Frameworks. Issue 35 (19th September 2017) - Bawari, Deependra; Prashanth, Billa; Jaiswal, Kuldeep; Choudhury, Angshuman Roy; Singh, Sanjay
Abstract : We have demonstrated stepwise functionalization of chlorophosph(III)azane, [ClP(µ‐N t Bu)]2 with organic azides and chalcogens (S and Se). The in situ 31 P 1 H NMR spectroscopic investigations reveal that conversion of the basic P III 2 N2 framework, leading to P V 2 N2 proceeds via (P III /P V )N2 intermediates. Under controlled conditions, the (P III /P V )N2 intermediate species can be isolated, providing details of the reaction pathway and distribution of the cis and trans isomers of the P V 2 N2 products. It has also been demonstrated that neat reactions at elevated temperatures expedite the formation of P V 2 N2 products, without significantly affecting the yields and relative distribution of the cis and trans isomers. All new compounds reported here are potential building blocks for the assembly of inorganic macrocycles and polymers. Abstract : Stepwise conversion of P–Cl to P(=E)–Cl centers in the basic [ClP(µ‐N t Bu)]2 has been studied using solvent, under neat conditions (E = S, Se, NAr), at elevated temperatures. The in situ 31 P 1 H NMR spectroscopic investigations reveal that the cis and trans isomers of [ClP(=E)(µ‐N t Bu)]2 are formed via the mixed‐valent [(E=)ClP(µ‐N t Bu)2 PCl] intermediates.